If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + y = 2x + 2 Reorder the terms: 2 + y = 2 + 2x Add '-2' to each side of the equation. 2 + -2 + y = 2 + -2 + 2x Combine like terms: 2 + -2 = 0 0 + y = 2 + -2 + 2x y = 2 + -2 + 2x Combine like terms: 2 + -2 = 0 y = 0 + 2x y = 2x Solving y = 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2x
| (2x+4)x(2x+4)= | | 2*2+7y=14 | | 3+y=-5 | | 3k+5=3k+1 | | (7+v)(2v-5)=0 | | -2x+9=3x-1 | | 24+18x=12+24x | | 4(9b+4)= | | 20n-24=0 | | 10=y/4-8 | | -2(b-9)+4b-18=-6 | | -x^2+9x-20= | | y/5+2=8 | | -4/7x=21,8 | | 24v^2-12v=0 | | -x^8(3x^5-5)= | | 6x-3x=-9 | | x/7+6=4x-27 | | -x^2+37x-20= | | -4x-3(3+2x)=-19 | | 2x+7=26(6+x)-4 | | -17-4=7n-6(2+n) | | -(9x^2-3x+3)= | | y=n^2-2n-3 | | -3x-10=x+14 | | 6x-5=4x-27 | | f(x)=4x+3x-3 | | x^2+-12x+20= | | -2(-13+3y)-y=-5 | | -3+8=-5z+6(z+8) | | -6x+4+4x=2 | | -53=-6x-4x-3 |